Ethnobotanical approach of medicinal plants in a rural community in the hinterland of Alagoas / Abordagem etnobotânica de plantas medicinais em uma comunidade rural do sertão alagoano - Janilo Italo Melo Dantas; Alicia Marques Torres (Universidade Estadual de Alagoas, 2019)
It is common to monitor the use of plants for medicinal purposes in various local populations. These have been one of the key features used as a medical strategy. Many of these individuals have developed a wide range of traditional knowledge, and they have been dispersed in several local populations. Therefore, this study aimed to analyze the knowledge of the residents of the community Lopes in Canapi, AL, on the use of medicinal plants, highlighting the purpose and their use. For data collection, semi-structured interviews were conducted with 30 individuals from the community, using the free listing technique, aiming to identify plants used as medicines, diseases combated by plants, ways of using them, and obtaining knowledge. The plants cited by the individuals were identified from specialized literature and through consultations with virtual herbaria. A total of 21 medicinal plants were reported, most frequently mint (Mentha spicata L.), mastruz (Chenopodium ambrosioides L.) and aloe (Aloe vera (L.). A wide variety of diseases treated by certain plants , from respiratory, digestive and cardiac diseases, among others.In relation to their use in the treatment of diseases, the leaves and the bark of the plants were the main means indicated.It was possible to perceive that the individuals of the community present a wide traditional knowledge medicinal, acquired socially from generation to generation.The accomplishment of this study allowed to register and to divulge the medicinal culture of the individuals, since many of the knowledge presented by the same, are essential in the cultural context and for the social life in which they are inserted.